Decision support for allocating farmed fish to customer orders using a bi-objective optimization model - Knudseth, Sunniva Haukvik; Molland, Even; Hoff, Arild; Hvattum, Lars Magnus; Oppen, Johan (Decision Making in Manufacturing and Services, 2022)
Aquaculture is an important industry in certain coastal areas. Focusing on farming of salmon and trout, an operational planning problem arises with the goal of allocating supply of fish to demand expressed through customer orders. This paper provides a conceptual model of such a planning problem, defines a corresponding bi-objective mathematical programming model. The problem is novel with respect to the structure of the transportation of fish, and the rules for satisfying customer orders with respect to fish size, quality, certification, and health status. Computational experiments are conducted to gain further insights into the use of the provided model to provide support for planners involved in the operational decision making. Results indicate that the bi-objective optimization model can be useful in situations where supply is insufficient to cover all the demand within a given planning horizon.